2020
DOI: 10.1136/rmdopen-2020-001402
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking patterns preceding primary Sjögren’s syndrome

Abstract: BackgroundCigarette smoking is a well-established risk factor for several autoimmune diseases, but its role in primary Sjögren’s syndrome (pSS) remains unclear. Here, we investigated the association between cigarette smoking and subsequent development of pSS.MethodsInformation on smoking habits was collected from lifestyle habit questionnaires of patients with pSS (n=815) and a matched control group (n=4425) for a case–control study. Differences in smoking exposure were analysed by conditional logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…For some diseases such as rheumatoid arthritis (RA), the link appears well established, whereas for others the relationship is more complex. As Dr. Kawada comments, 2 more recently published articles, using even larger numbers of patients than our population-based cohort on the relationship between smoking and pSS 3 and on SS among patients with RA, 4 confirmed the main finding of our study (i.e., the negative correlation between current smoking and SS); they also added other variables of potential interest such as the temporal smoking patterns preceding pSS diagnosis 3 and the association of age and female sex with SS in RA. 4 The relationship between smoking and disease occurrence may hold in both primary and secondary SS.…”
Section: Dr Berti Et Al Replysupporting
confidence: 78%
“…For some diseases such as rheumatoid arthritis (RA), the link appears well established, whereas for others the relationship is more complex. As Dr. Kawada comments, 2 more recently published articles, using even larger numbers of patients than our population-based cohort on the relationship between smoking and pSS 3 and on SS among patients with RA, 4 confirmed the main finding of our study (i.e., the negative correlation between current smoking and SS); they also added other variables of potential interest such as the temporal smoking patterns preceding pSS diagnosis 3 and the association of age and female sex with SS in RA. 4 The relationship between smoking and disease occurrence may hold in both primary and secondary SS.…”
Section: Dr Berti Et Al Replysupporting
confidence: 78%
“… 48–50 Also, positive associations of SS with chronic pulmonary disease and peripheral vascular disease may be explained by shared risk factors, such as cigarette smoking. 13 We also found that the magnitude of the association between herpes zoster and SS was significantly higher among those without comorbidities compared with those with CCI ≥1. It is possible that the influence of herpes zoster on SS was mitigated by the presence of competing risk factors as mentioned above among those with CCI ≥1 because of long development time before SS was diagnosed.…”
Section: Discussionsupporting
confidence: 55%
“…Although SS is identified to be a multifactorial disease, its risk factors and pathogenesis remain incompletely understood. However, its potential risk factors include endogenous genetic susceptibility with strongest association with the human leucocyte antigen locus,6–8 exogenous infection and environmental stimuli such as cigarette smoking and diet 9–13. B cell activation plays an important role in the pathogenesis of SS 14.…”
Section: Introductionmentioning
confidence: 99%
“…And third, smokers have a lower prevalence of focal sialadenitis in comparison with non-smokers. This Sjögren's-related smoking pattern seems to suggest that individuals who develop SS smoke equally as much as the general population during early life but are then more prone to stop (20), since the oral and ocular damage caused by tobacco smoke makes people with SS more likely to discontinue smoking (19). With respect to alcohol intake, patients with SS were less likely to consume alcohol after adjusting for age, sex and education in comparison with the general population (21), suggesting a similar pattern to that observed for smoking (oral discomfort from the intake of alcohol may underlie the lower prevalence in prevalent cases).…”
Section: Myth Smoking and Alcohol Intake May Enhance The Risk Of Sjög...mentioning
confidence: 96%